Fenomena Kawin Lari Dalam Perspektif Fiqh Munakahat Dan Adat Lokal Parmainan - Sutan Botung Hasibuan; Eka Pratiwi; Delisah Hasibuan; Rizki Elia Nasution; Zuipikar Abdul Hamid Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The phenomenon of elopement (marlojong) still frequently occurs in Parmainan society. This practice occurs when a woman is taken away to elope (marlojong) by another man. Prior to the elopement (marlojong), the woman had already been betrothed according to custom by another man. This type of research uses a qualitative descriptive method. Data collection was conducted through observation and interviews. The results of this study indicate that the resolution of elopement (marlojong) cases through traditional means is carried out through several mechanisms: First, through peaceful family and traditional channels. Second, through a marriage agreement to pay double the fine as a form of accountability. Third, if unsuccessful, they marry secretly. Fourth, some seek a marriage guardian in another location with a judge as the guardian. Meanwhile, the resolution of elopement cases (marlojong) through religious means has two approaches: First, through legal channels using a judge as the guardian if there is no parental consent. Second, the woman who eloped (marlojong) is separated from the man who took her away. Subsequently, the woman is married to her cousin according to the family's decision. From the perspective of local religious scholars, the resolution of elopement (marlojong) in Paramai fundamentally violates religious principles because it involves taking someone else's child to another place without parental consent (guardian). From an Islamic legal standpoint, the practice of elopement (marlojong) in Paraminan contradicts Islamic law.